2013
DOI: 10.1074/jbc.m113.499004
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1/γ-Secretase Controls Glutamate Release, Tyrosine Phosphorylation, and Surface Expression of N-Methyl-d-aspartate Receptor (NMDAR) Subunit GluN2B

Abstract: Background: Presenilin-1/␥-secretase is critical to neuronal function. Results: Inhibition of presenilin-1/␥-secretase increases release of glutamate, stimulating NMDAR and calpain while decreasing phosphorylation and surface expression of neuronal GluN2B. Conclusion: Presenilin-1/␥-secretase regulates glutamate release, NMDAR-dependent calpain activity, and modification of GluN2B. Significance: This study reveals a role for ␥-secretase in release of glutamate, a neurotransmitter central to neuronal function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Because CREB activity is regulated by NMDARs (42,52), we asked whether the PS1/g-secretase system might affect CREB activity via this receptor. This possibility is also supported by reports that the reduction of PS1 or the inhibition of g-secretase reduce cell surface expression of NMDAR (41,53) and that NMDAR currents are affected by PS1 Figure 6. PS1/g-secretase regulates CREB activation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Because CREB activity is regulated by NMDARs (42,52), we asked whether the PS1/g-secretase system might affect CREB activity via this receptor. This possibility is also supported by reports that the reduction of PS1 or the inhibition of g-secretase reduce cell surface expression of NMDAR (41,53) and that NMDAR currents are affected by PS1 Figure 6. PS1/g-secretase regulates CREB activation.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, it was reported that the absence of PS1 or the inhibition of g-secretase activity activates the NMDA receptor (NMDAR) (41), and literature indicates that CREB activity is modulated by NMDAR (42). To further examine the effects of the NMDAR-CREB signaling cascade, we thus used MK801, an antagonist of NMDAR, to investigate whether blocking NMDAR changed CREB phosphorylation.…”
Section: Nmda Receptor Antagonists Abolish Creb Activation and Supprementioning
confidence: 99%
“…All animal experiments were carried out according to regulations of Mount Sinai Medical Center. Primary cortical neuronal cultures (PCNC) were prepared from embryonic day (E) 15.5 mouse embryo brains, plated on poly‐ d ‐lysine‐coated plates in Neurobasal medium as reported elsewhere (3, 28, 29) and kept in vitro before use as indicated in figure legends. At 9 d in vitro (DIV), postmitotic neurons represented more than 95% of cultured cells (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…GRN) overnight. The next day, the medium was switched to HBSS containing Hb‐EGF, EGF, or PGRN for 30 min, followed by 50 μM glutamate incubation for 3 h, and cell viability was evaluated by MTT assay and normalized to nontreated cells, as previously described (3, 29). No significant effect compared to nontreated was observed when growth factors alone were added to cultures.…”
Section: Methodsmentioning
confidence: 99%
“…were prepared from E 15.5 mouse embryo brains, plated on poly-D-lysine-coated plates in Neurobasal medium as reported (3,28,29) and kept in vitro before use as indicated in figure legends. At 9 days in vitro (DIV) postmitotic neurons represent more than 95% of cultured cells (3 and Supplementary Fig.…”
Section: Cell Culturesmentioning
confidence: 99%